2018
DOI: 10.14778/3282495.3282501
|View full text |Cite
|
Sign up to set email alerts
|

<u>S</u>tart <u>l</u>ate or <u>f</u>inish <u>e</u>arly

Abstract: Graph processing systems are important in the big data domain. However, processing graphs in parallel often introduces redundant computations in existing algorithms and models. Prior work has proposed techniques to optimize redundancies for out-of-core graph systems, rather than distributed graph systems. In this paper, we study various state-of-the-art distributed graph systems and observe root causes for these pervasively existing redundancies. To reduce redundancies without sacrificing parallelism, we furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…At 24 weeks gestation, from a volume of amniotic fluid of approximately 600 ml surrounding the fetus [32], a 10-ml aliquot obtained by amniocentesis avoids the inherent risk of hemorrhage, preterm labor, and fetal demise associated with a fetal skin or placenta biopsy [7]. An amniocentesis also has virtually no added morbidity because it is often a recommended test conducted in the prenatal workup of a major cardiac anomaly to rule out an abnormal karyotype [33]. Furthermore, our group, among others [34], has previously shown that amniotic fluid cells can be harvested without maternal cell contamination and are therefore derived exclusively from the fetus [10].…”
Section: Discussionmentioning
confidence: 99%
“…At 24 weeks gestation, from a volume of amniotic fluid of approximately 600 ml surrounding the fetus [32], a 10-ml aliquot obtained by amniocentesis avoids the inherent risk of hemorrhage, preterm labor, and fetal demise associated with a fetal skin or placenta biopsy [7]. An amniocentesis also has virtually no added morbidity because it is often a recommended test conducted in the prenatal workup of a major cardiac anomaly to rule out an abnormal karyotype [33]. Furthermore, our group, among others [34], has previously shown that amniotic fluid cells can be harvested without maternal cell contamination and are therefore derived exclusively from the fetus [10].…”
Section: Discussionmentioning
confidence: 99%
“…For the collagen-only ECM, treatment with each of the CXCL12 isoforms resulted in multicellular extensions or sprouts from the endothelial layer at the vessel/ECM interface ( Figure 3A). In contrast, for the collagen/HA ECM, treatment with the individual CXCL12 isoforms promoted sheet-like migration of the endothelial cells that was reminiscent of local vessel dilation [31] ( Figure 3B). We further characterized this vessel dilation response by analyzing the total area displacement of the HUVEC monolayer into the collagen/HA ECM during the course of the experiments ( Figure S1, Supporting Information).…”
Section: Sprouting Angiogenesis Mediated By Cxcl12 Isoforms Is Continmentioning
confidence: 98%
“…In negative VEGF gradients, a process resembles vessel dilation occurred as the ECs spread into a sheet-like formation. [82] These studies show that the dosage, gradient profile, and timing of the addition of the growth factors all affect the outcome of the tissue vascularization in vitro.…”
Section: Chemical Factor: Growth Factorsmentioning
confidence: 96%